PENGEMBANAN FILSAFAT PANCASILA DALAM SISTEM PEMIDANAAN DI INDONESIA - Dahwir, Ali (Faculty of Law, University of Palembang, 2019)
In general, the system of imposing crimes against perpetrators of criminal acts applied in Indonesia still refers to the criminal system which was abandoned by the Dutch Colonial based on liberalism, this is due to the absence of regulations made by Indonesia that specifically establish the criminal system. So that the criminal system that runs is not based on the local wisdom of the Indonesian people which ultimately does not reflect the values ​​of Pancasia as a source of all legal sources. The purpose of this paper is to examine the development of the philosophy of Pancasila in the penal system. This research is normative, using secondary data, with a legal philosophy and concept approach. Qualitatively analyzed to find links between criminal prosecution in Indonesia and the adoption of Pancasila values